Clinical, Immunological, and Genetic Features in 49 Patients With ZAP-70 Deficiency: A Systematic Review - Sharifinejad, Niusha; Jamee, Mahnaz; Zaki-Dizaji, Majid; Lo, Bernice; Shaghaghi, Mohammadreza; Mohammadi, Hamed; Jadidi-Niaragh, Farhad; Shaghaghi, Shiva; Yazdani, Reza; Abolhassani, Hassan; Aghamohammadi, Asghar; Azizi, Gholamreza (Frontiers in Immunology, 2020)
Background: Zeta-Chain Associated Protein Kinase 70 kDa (ZAP-70) deficiency is a novel combined immunodeficiency (CID) caused by recessive homozygous/compound heterozygous loss-of-function mutations in the ZAP70 gene. Patients with ZAP-70 deficiency present with a variety of clinical manifestations, particularly recurrent respiratory infections and cutaneous involvements. Methods: We searched PubMed, Web of Science, and Scopus databases for all reported ZAP-70 deficient patients and screened against the described eligibility criteria. A total of 49 ZAP-70 deficient patients were identified from 86 articles. For all patients, demographic, clinical, immunologic, and molecular data were collected. Results: ZAP-70 deficient patients have been reported in the literature with a broad spectrum of clinical manifestations including recurrent respiratory infections (61.2%), cutaneous involvement (44.9%), lymphoproliferation (24.5%), autoimmunity (14.3%), enteropathy (14.3%), and increased risk of malignancies (6.1%). The predominant immunologic phenotype was low CD8+ T cell counts (89.8%). Immunologic profiling showed defective antibody production (>60%) and decreased lymphocyte responses to mitogenic stimuli such as phytohemagglutinin (89.7%). Mutations of the ZAP70 gene were located throughout the gene, and there was no mutational hot spot. However, the splice site mutation c.1624-11G>A (p.K541_K542insLEQ), located in the kinase domain, was the most frequent mutation (found in 10 families). Hematopoietic stem cell transplantation (HSCT) was applied as the major curative treatment in 25 (51%) of the patients, 18 patients survived transplantation, while two patients died and three required a second transplant in order to achieve full remission. Conclusion: Newborns with consanguineous parents, positive family history of CID, and low CD8+ T cell counts should be considered for ZAP-70 deficiency screening, since early diagnosis and treatment with HSCT can lead to a more favorable outcome. Based on the current evidence, there is no genotype-phenotype correlation in ZAP-70 deficient patients.